2013
DOI: 10.5142/jgr.2013.37.341
|View full text |Cite
|
Sign up to set email alerts
|

An approach for simultaneous determination for geographical origins of Korean Panax ginseng by UPLC-QTOF/MS coupled with OPLS-DA models

Abstract: Identification of the origins of Panax ginseng has been issued in Korea scientifically and economically. We describe a metabolomics approach used for discrimination and prediction of ginseng roots from different origins in Korea. The fresh ginseng roots from six ginseng cooperative associations (Gangwon, Gaeseong, Punggi, Chungbuk, Jeonbuk, and Anseong) were analyzed by UPLC-MS-based approach combined with orthogonal projections to latent structure-discriminant analysis multivariate analysis. The ginsengs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…These factors may affect secondary metabolites qualitatively and quantitatively, so their bioactivities could be varied [21][22][23]. Therefore, metabolite profiling studies of herbal plants is very important for ensuring their safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…These factors may affect secondary metabolites qualitatively and quantitatively, so their bioactivities could be varied [21][22][23]. Therefore, metabolite profiling studies of herbal plants is very important for ensuring their safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…And the permutation test demonstrated that the OPLS‐DA model was reliable because the slope of both R2 and Q2 regression curve was almost near 1 (Fig. b; Song et al ., ; Triba et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…And the permutation test demonstrated that the OPLS-DA model was reliable because the slope of both R2 and Q2 regression curve was almost near 1 ( Fig. 3b; Song et al, 2013;Triba et al, 2015). Figure 3c shows the corresponding loading plot of the tea samples using the volatile compounds as variable.…”
Section: Multivariate Statistical Analyses Of Volatile Compoundsmentioning
confidence: 92%
“…Currently, metabolomics tools (i.e., statistical and multivariate data) are essential for studying various aspects of natural products and plant metabolites including dereplication, biological activity screening, chemotaxonomy, and quality control [9][10][11][12][13][14]. Ultraperformance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTof MS)-based metabolomics is useful for the rapid and highly sensitive detection of secondary metabolites from plant biosynthesis pathways [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, technologies that use high-resolution mass spectrometry (HRMS) have improved detection and quantification strategies of assessing structural information to reveal diverse metabolites. In addition, various plants (e.g., Agastache rugose, Spinacia oleracea, Sophora flavescens, Panax ginseng, Euphorbia supine, and Hordeum vulgare) have been investigated using UPLC-QTof MS [9][10][11][12][13][14]. Specifically, the physiological changes of many flavonoids was depend on the cultivation conditions using temperatures, light, drought, salt, biotic stresses, genetics, and agronomic conditions [8,10].…”
Section: Introductionmentioning
confidence: 99%